Zornia latifolia: a smart drug being adulterated by Stylosanthes guianensis - Cornara, L.; Fortuna-Perez, A. P. [UNESP]; Bruni, I.; Salis, A.; Damonte, G.; Borghesi, B.; Clericuzio, M. (Springer, 2018)
Dried herbal preparations, based on Zornia latifolia, are commonly sold on web, mainly for their supposed hallucinogenic properties. In this work, we demonstrate that these commercial products contain a different Fabacea, i.e., Stylosanthes guianensis, a cheaper plant, widely cultivated in tropical regions as a fodder legume. We were provided with plant samples of true Zornia latifolia from Brazil, and carried out a thorough comparison of the two species. The assignment of commercial samples was performed by means of micro-morphological analysis, DNA barcoding, and partial phytochemical investigation. We observed that Z. latifolia contains large amounts of flavonoid di-glycosides derived from luteolin, apigenin, and genistein, while in S. guianensis lesser amounts of flavonoids, mainly derived from quercetin, were found. It is likely that the spasmolytic and anxiolytic properties of Z. latifolia, as reported in traditional medicine, derive from its contents in apigenin and/or genistein.
Keywords: Smart drugs; Morphologic analysis; DNA barcoding; Luteolin; Apigenin; Genistein